Fractional matching preclusion for crossed cubes - Zou, Jinyu; Ye, Chengfu; Wu, Miaolin; Zhang, Shumin (Utilitas Mathematica, 2020)
Suppose F be an edge set and F' a subset of edges and/or vertices of a graph G, then F is a fractional matching preclusion(FMP) set and F' is a fractional strong matching preclusion (FSMP) set if G - F and G - Fr contains no fractional perfect matching. The FMP(FSMP) number of G is the minimum size of FMP(FSMP) sets of G. In this paper, we obtain the FMP and FSMP number for the crossed cubes. In addition, all the optimal fractional strong matching preclusion sets of these graphs are categorized,. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.